Tools of the Trade: Point-of-Care Ultrasonography as a Stethoscope - Sekiguchi, Hiroshi (Seminars in Respiratory and Critical Care Medicine, 2016)
Since the advent of portable ultrasonography machines, many providers, including intensivists and pulmonologists, have been trained in point-of-care ultrasonography. When point-of-care ultrasonography is performed with focused clinical question and goal in mind, it serves as a valuable adjunct to physical examination and facilitates patient care and disease management. Its clinical application is now wider than that of a stethoscope in the intensive care unit where the noise level is high. In this review article, crucial ultrasonographic findings, their clinical implication, and their limitations are discussed in the most commonly targeted organ systems: cardiac, thoracic, abdominal, and vascular. In addition, recent studies on the use of multiorgan system point-of-care ultrasonography in diagnoses and management of acutely ill patients are described. As new clinical applications have been identified, a conventional approach to the critical illness must be modified to a new approach that incorporates ultrasonographic information. Clinicians should not only be trained in image acquisition and interpretation but also be up to date on the new ultrasonography-guided diagnosis, therapy, and management.
Keywords: critical illness; ultrasonography; echocardiography; Point-of-Care Ultrasonography